Congenital constriction band syndrome: a case report - Kumar, Sunil; Marwah, Poonam; Marwah, Ashish; Arya, Ashish (International Journal of Research in Medical Sciences, 2018)
Congenital constriction bands are anomalous bands formed during antenatal period that encircle a digit or an extremity in a fetus leading to a wide spectrum of manifestations, ranging from shallow grooves to acrosyndactyly and amputations. It is also associated with skeletal and other birth defects like craniofacial abnormalities, spinal dysraphism, porencephaly, hydrancephaly and visceral body wall malformations. We hereby present one such case which presented to us with below knee amputation of the lower limb and syndactyly.